2014
DOI: 10.3109/09546634.2014.933166
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adalimumab in psoriatic patients previously treated with etanercept in a real-world setting

Abstract: Previous etanercept failure seems not influence the success and safety of adalimumab treatment in moderate to severe plaque psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The first point of strength of our study consists in having observed a large cohort of patients and having considered all the switches that occurred in the follow-up period. Indeed, many studies in the literature focus on a specific switch, from etanercept to infliximab [ 24 , 27 , 28 ], from etanercept to adalimumab [ 22 , 23 , 29 , 30 ], etc., and are based on data collected in a single hospital; larger studies that consider all switches, from any PSObio drug to any PSObio drug, usually only consider the first switch for each patient [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first point of strength of our study consists in having observed a large cohort of patients and having considered all the switches that occurred in the follow-up period. Indeed, many studies in the literature focus on a specific switch, from etanercept to infliximab [ 24 , 27 , 28 ], from etanercept to adalimumab [ 22 , 23 , 29 , 30 ], etc., and are based on data collected in a single hospital; larger studies that consider all switches, from any PSObio drug to any PSObio drug, usually only consider the first switch for each patient [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in baseline characteristics of the patient populations or in the pre-treatments and statistical analysis applied. A recent study by Fonseca et al 10 addressed the influence of previous etanercept failure on the effectiveness and safety of adalimumab in psoriasis patients in a real-world setting. Authors concluded that previous etanercept failure does not seem to jeopardize the success and safety of subsequent adalimumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Primary failure was defined as an insufficient response (patients not achieving PASI 50) at week 12-16, according to the medication. Secondary failure was defined as the loss of response (PASI [ 50% of initial value) in a patient who had previously achieved PASI 50 response at week 12-16 [8].…”
Section: Methodsmentioning
confidence: 99%